A comparison of use microdebrider with conventional endoscopic surgery for nasal polyps - Ibrahem, Sarah Emad; Ibrahem, Mostafa Hamza; Ali, Yasser Mouhammad (Journal of medical and pharmaceutical sciences, 2022)
Background: Nasal polyps are chronic and benign inflammatory lesions that arise from the mucous membrane of the nasal cavity and paranasal sinuses. And it represents a challenge in treatment due to its uncertain causes and recurrent relapse. Because of that the surgical treatment is considered as the best choice for the removal of nasal polyps. And, it contains endoscopic sinus surgery using either conventional instruments or the microdebrider which is an automatic device used to remove the obstructing tissue. And, it represents a modern technology in the treatment of nasal polyps. Objectives: Studying and comparing the microdebrider assisted endoscopic surgery and conventional methods using sinus endoscopes in the surgical management of nasal polyps, and evaluating the advantages of the microdebrider. Methods: The study was a comparative prospective study conducted at the department of ENT, tishreen university hospital, lattakia, Syria done between 2020 to 2021. 76 patients (46 male and 30 females) were enrolled in the study and divided into two groups depending on the used surgical method. Group1: conventional endoscopic sinus surgery method, Group2: microdebrider assisted endoscopic surgery. Then, comparing the results during and after 3 months of the surgery. Results: There were a significant difference between study groups in the mean time required for surgery (shorter in group2 with p-value <0.01) and the average intraoperative blood loss (less in group2 with p-value<0.01). Endoscopic sinus surgery with the microdebrider noted a low rate of postoperative synechiae formation after three monthes and there is no significant difference between the two groups in recurrence of nasal polyps after three monthes. Conclusion: Using the microdebrider in the surgical treatment of nasal polyposis is an effective and safe method because it has the advantage of saving time, decreasing blood loss during surgery, and reducing the rate of postoperative synechiae formation. but there is no significant difference in recurrence between the microdebrider and conventional methods.